Pelaksanaan Tugas Pembantu Pegawai Pencatat Nikah Pasca Instruksi Dirjen Bimas Islam Nomor DJ.II/1 Tahun 2015 - Firdaus, Ali (Universitas Islam Negeri Raden Intan Lampung, 2017)
The Ministry of Religious Affairs decided not to extend the term of Assistant Employee of Marriage Registerer (PPPN). Then the Directorate General of Islamic Guidance issued the Instruction Letter No. DJ.II / 1 Year 2015 on the Appointment of the Marriage Officer. The PPPN appointment recommendation that KUA is included in typology D1 and D2, ie: the subdistrict area is not reachable by the marriage officer and the limited of human resources. This problems arise in a number of regions in Indonesia, and also in Lampung Province. This research finds that after the instruction of the Director General of Islamic Guidance, PPPN in KUA Natar, Padang Cermin, Tanjung Karang Pusat and Marga Punduh can be concluded as follows: Since that enactment, PPPN at KUA Tanjung Karang Bandar Lampung is no longer perform the duties. While in KUA District Natar, KUA District Padang Cermin and KUA District Marga Punduh partially PPPN still carry out the task of recording marriage.